Metformin protects PC12 cells and hippocampal neurons from H2O 2‐induced oxidative damage through activation of AMPK pathway. Issue 9 (19th February 2019) - Zhao, Xia; Zeng, Zhiwen; Gaur, Uma; Fang, Jiankang; Peng, Tangming; Li, Shuai; Zheng, Wenhua
Abstract: Metformin, a first line anti type 2 diabetes drug, has recently been shown to extend lifespan in various species, and therefore, became the first antiaging drug in clinical trial. Oxidative stress due to excess reactive oxygen species (ROS) is considered to be an important factor in aging and related disease, such as Alzheimer's disease (AD). However, the antioxidative effects of metformin and its underlying mechanisms in neuronal cells is not known. In the present study, we showed that metformin, in clinically relevant concentrations, protected neuronal PC12 cells from H2 O2 ‐induced cell death. Metformin signiﬁcantly ameliorated cell death due to H2 O2 insult by restoring abnormal changes in nuclear morphology, intracellular ROS, lactate dehydrogenase, and mitochondrial membrane potential induced by H2 O2 . Hoechst staining assay and flow cytometry analysis revealed that metformin significantly reduced the apoptosis in PC12 cells exposed to H2 O2 . Western blot analysis further demonstrated that metformin stimulated the phosphorylation and activation of AMP‐activated protein kinase (AMPK) in PC12 cells, while application of AMPK inhibitor compound C, or knockdown of the expression of AMPK by specific small interfering RNA or short hairpin RNA blocked the protective effect of metformin. Similar results were obtained in primary cultured hippocampal neurons. Taken together, these results indicated that metformin is able to protect neuronal cells from oxidative injury, at least in part, via the activation of AMPK. As metformin is comparatively cheaper with much less side effects in clinic, our findings support its potential to be a drug for prevention and treatment of aging and aging‐related diseases. Abstract : Metformin protects PC12 cells and hippocampal neurons from H2 O2 ‐induced oxidative damage. AMP‐activated protein kinase (AMPK) mediated the protective effects of metformin in PC12 cells and hippocampal neurons.